2020
DOI: 10.3417/2020601
|View full text |Cite
|
Sign up to set email alerts
|

The Central Role of Taxonomy in the Study of Neotropical Biodiversity

Abstract: The Neotropics are the most species-rich area of the planet. Understanding the origin and maintenance of this diversity is an important goal of ecology and evolutionary biology. Success in this endeavor relies heavily on the past work of taxonomists who have collected specimens and produced the floras and monographs that constitute the foundation for the study of plant diversity. To illustrate this, we visualize collecting efforts through time and identify the importance of past taxonomic and collection effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 195 publications
0
20
0
1
Order By: Relevance
“…Nonetheless, a proper assessment of the biodiversity within Mexico remains distant, mainly because of the global taxonomy crisis associated with the fact that many new barcodes have not been matched with their corresponding species. To overcome this taxonomic impediment has particular relevance in the neotropics, the most species-rich region in the world [11]. Consequently, we consider the best practice is to document the specimens studied with vouchers deposited in museums.…”
Section: Figurementioning
confidence: 99%
“…Nonetheless, a proper assessment of the biodiversity within Mexico remains distant, mainly because of the global taxonomy crisis associated with the fact that many new barcodes have not been matched with their corresponding species. To overcome this taxonomic impediment has particular relevance in the neotropics, the most species-rich region in the world [11]. Consequently, we consider the best practice is to document the specimens studied with vouchers deposited in museums.…”
Section: Figurementioning
confidence: 99%
“…Gentry (1982) concluded that the explanation for the much greater diversity in the Neotropics lay in understanding diversification patterns in epiphyte, palmetto, and understory shrub lineages of montane forests in the Andes, as these comprised the bulk of taxonomic diversity and seemed to represent rapid radiations. Despite centuries of study, and recent decades of phylogenetic research, Neotropical and Andean diversity remains poorly described and understood (Ulloa et al 2004; Hopkins 2007; Goodwin et al 2015; Mutke and Weigend 2017; Zizka et al 2018; Lagomarsino and Frost 2020). Thus, elucidating evolutionary patterns in Andean-centered cloud forest lineages remains a key step toward understanding the disparity in species richness between the Neotropics and other tropical ecoregions.…”
mentioning
confidence: 99%
“…As an enterprise underpinning all biological and even some cultural research, monography offers uniquely transformative opportunities for the global collaboration of individuals from different fields and cultures (Tachibana, 2019;Lagomarsino & Frost, 2020). Nonetheless, we must acknowledge how the historic and ongoing role of colonialism and racism within our own institutions exerts significant influence on the practice of monographic work, limiting this practice to those with access to global resources, and to the detriment of the field.…”
Section: Recognition: Appropriate Valuation and Resourcing Of Monographic Workmentioning
confidence: 99%
“…Many allied fields (i.e., phylogenetics, anatomy and physiology, ecology, toxinology, computational biology, population genetics, comparative genetics and genomics) are not well-integrated with monographic work, with researchers in well-aligned fields often unaware of existing monographs or not fully aware of their relevance or scientific value. This lack of integration may complicate the interpretation of ecological, physiological, or biological data (Bortolus, 2008;Vink et al, 2012;Prié et al, 2012;Daglio andDawson, 2019, Lagomarsino andFrost 2020), but also means that there are many unrealized opportunities for comparative studies. Collaborative monographs are clearly in the realm of hypothesis-testing research, as they include species delimitations (Valdecasas et al, 2014), comparative analyses, and phylogenetic inferences (e.g., Magalhães et al, 2017;Cui et al, 2019;Mandiwana-Neudani et al, 2019).…”
Section: Support: Building Interdisciplinary Relationships and Successionmentioning
confidence: 99%